IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER (PPK) MELALUI PEMBIASAAN KARAKTER ASWAJA(PKA) PADA MADRASAH IBTIDAIYAH - Novita Ayu Dewantari; Firda Zakiyatur Rofi’ah; Suttrisno (Journal Education Innovation (JEI), 2024)
Education plays a crucial role in forming character, especially with the 2013 Curriculum (K13) which emphasizes character formation as a solution to overcome the current low character of the Indonesian nation. Through the implementation of the Character Education Strengthening Policy (PPK), efforts are made to strengthen student character by involving the active role of educational institutions, families and communities, which as a whole are part of the National Mental Revolution Movement (GNRM). MINU Walisongo is one of the leading madrasas in Bojonegoro district which is based on Nahdlatul Ulama and has implemented a character strengthening education program. Character Strengthening Education (PPK) efforts in the K13 curriculum are through Aswaja Character Habituation (PKA). Habituation of the Aswaja Character is a form of instilling the Aswaja or NU character in an amaliyah manner in students.. The aim of this research is to find out Implementation of Strengthening Character Education (PPK) through Aswaja Character Habituation (PKA) at MINU Unggulan Walisongo. The results of this study show that Implementation of Strengthening Character Education at MINU Unggulan Walisongo Sumberrejo through the Aswaja Character Habituation (PKA) program on religious values ​​is found in the activity of chanting Sholawat: Munjiyat, Fatih, Tibbil Qulub, Qulil Anwar, Nariyah and NU, then chanting Asmaul Husna, Istinghotsah, tahlil and Aqidatul Lay people who are included in the Aswaja Tawazun charity.